2021
DOI: 10.1161/circ.144.suppl_1.10078
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 10078: Facilitators and Barriers to Chronic Care Among Patients with Heart Failure in Rural Haiti: A Qualitative Study

Abstract: Introduction: Heart failure (HF) is a leading cause of hospitalizations in rural Haiti. However, few patients hospitalized for HF return for outpatient care. The factors that contribute to chronic HF care access are poorly understood. Objective: To investigate the facilitators and barriers to accessing care for chronic HF from the patients’ perspectives. Methods: We conducted three group interviews and one i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, suggestions from multiple socioecological levels indicated that increasing programme education and support, increased sport-specific activities and improved awareness of preventive effects, influence NMT implementation success 36 88 89 115 116 Figure 2,. adapted from Basow et al 117 illustrates the contextual factors reported in the literature 117. This evidence-informed model shows the important barriers and facilitators that influence the end-user implementation of NMT warm-up programmes across the three key socioecological levels of change.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, suggestions from multiple socioecological levels indicated that increasing programme education and support, increased sport-specific activities and improved awareness of preventive effects, influence NMT implementation success 36 88 89 115 116 Figure 2,. adapted from Basow et al 117 illustrates the contextual factors reported in the literature 117. This evidence-informed model shows the important barriers and facilitators that influence the end-user implementation of NMT warm-up programmes across the three key socioecological levels of change.…”
Section: Resultsmentioning
confidence: 94%